Using P-Star model to linking money and prices in a financial liberalised developing economy: The case for Malaysia - Muzafar Shah Habibullah, (Penerbit Universiti Kebangsaan Malaysia, 1999)
The P-Star approach of modelling inflation proposed by Hallman et al. has been widely tested in the United States and other developed countries. The applicability of the P-Star model for the developing countries is yet to be determined. The main prupose of the present study is to add to the current literature on the robustness of the P-Star model with respect to a developing country - Malaysia. Using a sample period from 1981:1 to 1994:4, our results suggest that Malaysian monetary data support the P-Star model. We conclude that there is a close relationship between money and the price level in Malaysia despite the occurences of financial liberalisation in the 1980s and 1990s